Reconstruction of Islamic Family Law in Indonesia Through Constitutional Court Decisions - Najichah, Najichah (Universitas Islam Negeri Walisongo Semarang, 2022)
No law is perfect as well as in the Marriage Law, there are many criticisms of the articles in the UUUP which are considered not to follow the spirit of family law reform. Many articles are considered discriminatory, have multiple interpretations, and do not provide legal justice. The proposed revision of the contents of the UUP began during the Reformation period, but the debate just ended. Amid the impasse in 2003 the Constitutional Court (MK) was born as one of the judicial institutions in Indonesia through the amendment of the 1945 Constitution. The birth of the Constitutional Court gave fresh air to groups who felt that their constitutional rights were violated by Marriage Law No.1 of 1975. This research is a descriptive-analytic library research, the problem approach used is a normative-juridical approach. The results of the study found that the Constitutional Court acted as an interpreter, and reinforcer changed Islamic family law, and even made a new Islamic family law using the glasses of the constitution. Based on the decision of the Constitutional Court which is final and binding, the Constitutional Court's decision functions as a negative legislator and a positive legislator as in Decision No.46/PUU-VIII/2010, Decision No.69/PUU-XIII/2015 and Decision No.22/PUU- XV/2017. In addition, the Constitutional Court also provides interpretation and strengthening of Islamic family law as stated in decision No.68/PUU/XII/2014. Based on the four decisions of the Constitutional Court, the Constitutional Court has an important and effective role in reforming Islamic family law in Indonesia.Undang-undang tidak ada yang sempurna begitu pula dalam UU Perkawinan, banyak kritisi tentang pasal-pasal dalam UUP yang dianggap tidak sesuai dengan semangat pembaharuan hukum keluarga. Banyak pasal yang dianggap diskriminatif, multitafsir dan tidak memberikan keadilan hukum. Sesungguhnya usulan revisi terhadap isi UUP sudah mulai pada masa Reformasi, namun perdebatan tersebut berhent begitu saja. Di tengah kebuntuan tersebut pada tahun 2003 Mahkamah Konstitusi (MK) lahir sebagai salah satu lembaga yudisial di Indonesia melalui amandemen UUD45. Lahirnya MK memberikan angin segar bagi kelompok yang merasa hak-hak konstitusi dilanggar dengan adanya UU Perkawinan No.1 tahun 1975. Penelitian ini merupakan jenis penelitian pustaka (library research) bersifat deskriptif-analitik, pendekatan masalah yang digunakan adalah pendekatan normatif-yuridis. Hasil penelitian menemukan MK berperan sebagai penafsir, penguat, mengubah hukum keluarga Islam bahkan membuat hukum keluarga Islam yang baru dengan mengunakan kacamata kontitusi. Berdasarkan putusan MK yang bersifat final and binding maka putusan MK berfungsi sebagai negatif legislator dan postitif legislator sebagaimana dalam putusan Putusan No.46/PUU-VIII/2010, Putusan No.69/PUU-XIII/2015 dan Putusan No.22/PUU-XV/2017. Selain itu MK juga memberikan penafsiran dan penguatan hukum keluarga Islam sebagaimana dalam putusan No.68/PUU/XII/2014. Berdasarkan empat putusan MK maka MK mempunyai peranan yang penting dan efektif dalam pembaharuan hukum keluarga Islam di Indonesia.